EVALUASI PROMOSI DI PERPUSTAKAAN SOEMAN HS PEKANBARU - Yuhelmi, Yuhelmi; H., Rosman (Universitas Lancang Kuning, 2015)
This study aims to reveal how promotion has been done by Soeman HS Library staff in increasing the number of visitor. This is done to see how the campaign was carried out and what constraints were encountered when the promotion was conducted and to find out how and what was being done to overcome these obstacles, what kind of promotion has or has not been done to increase the number of visitors. Additionally, the results of this study determines what kind of promotion should be improved and maintained for future development to increase the number of visitors in the library. The staff who have involved in the promotion of the library. The ultimate goal of this research is to evaluate what promotion has been done and how the next promotion can be applied to increase the number of visitors.